DETERMINASI EASE OF USE DAN SECURITY TERHADAP MINAT PENGUNAAN E-WALLETS PADA MASYARAKAT HAMPARAN RAWANG - Baviga, Rio; Putri, Rizka Khairani (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
The rapid growth of digital technology has increased the use of digital wallets, including among the community in Hamparan Rawang. However, not all individuals immediately shift to cashless transactions, as many still consider factors such as ease of use and security before adopting digital wallet services. This study aims to examine the extent to which these two factors influence the community’s interest in using digital wallets. This research employs a quantitative approach by distributing questionnaires to 99 respondents selected through purposive sampling. The collected data were analyzed using SPSS through validity tests, reliability tests, t-tests, and F-tests. The results indicate that ease of use has a positive and significant effect on user interest, suggesting that simple, easy-to-understand, and accessible applications encourage higher user engagement. Security also shows a significant influence, as features such as data protection, PIN/OTP verification, and transaction notifications help users feel safer when performing digital transactions. Furthermore, both variables jointly show a strong and significant impact on the interest in using digital wallets.Overall, this study highlights that users are more likely to use digital wallets when the services offered are not only easy to operate but also provide a sense of security in every transaction.